Exploring the Metabolic Vulnerabilities of Epithelial–Mesenchymal Transition in Breast Cancer - Sun, Xiangyu; Wang, Mozhi; Wang, Mengshen; Yao, Litong; Li, Xinyan; Dong, Haoran; Li, Meng; Li, Xiang; Liu, Xing; Xu, Yingying (Frontiers in Cell and Developmental Biology, 2020)
Metastasis and drug resistance are the leading causes of death for breast cancer patients. Epithelial-mesenchymal transition (EMT), a transition from polarized epithelial cells to motile mesenchymal cells mediated by a series of activation signals, confers breast tumor cells with enhanced stem cell, invasive and metastatic properties. Metabolic reprogramming is an emerging hallmark of cancer cells, which have a complex mutual effect with EMT process. Under hypoxic and nutrient-deprived condition, metabolic rewiring can rapidly provide ATP and sufficient metabolic intermediates for fueling breast cancer metastasis and progression. In this review, we primarily focus on how these altered metabolic phenotypes of breast tumor cells activate the EMT transcription factors and induce EMT process to further promote metastasis and resistance to therapy. This review is divided to glucose, lipid and amino acid metabolism to explore for potential metabolic vulnerabilities, which may provide new insights for blocking EMT process in breast cancer.